ANALISIS HUKUM ISLAM TERHADAP PELAKSANAAN PENYEMBELIHAN AYAM DI PASAR PON KABUPATEN JOMBANG - Bambang Irawan (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2016)
Halal food is one of the factors considered by the Muslims in their food consumption. In consumption from animal-food, halal is seen since of how the slaughtering process. In Pasar Pon Jombang there are several places to slaughter the fowl. For various reasons , among which include bustle, practicality or dare to slaughtering chickens, the people who entrust consumed in the Pasar Pon sure that officers and slaughter process in accordance with the rules of Islam. Therefore, halal slaughter results come guaranteed. Keywords : Islamic Law, Slaughter Chicken, Pasar Pon Jombang .